Bioassay-Guided Isolation of Antimicrobial Compounds from Marine Sponge Neopetrosia exigua (Journal of Basic and Applied Research in Biomedicine, 2024)
The marine sponge Neopetrosia exigua has shown great potential as a source of bioactive compounds with significant antimicrobial properties. This study applied bioassay-guided fractionation to isolate and evaluate the antimicrobial activities of various compounds from N. exigua collected off the coast of Langkawi Island, Malaysia. Methanol extracts were partitioned into different fractions, with dichloromethane (CH₂Cl₂) and n-butanol (n-BuOH) fractions exhibiting the most potent antimicrobial activities. Four compounds were isolated: a previously undescribed bisulphate avarol derivative (1), two compounds isolated for the first time from N. exigua isohyrtiosine A (2) and demethylcystalgerone (3) and xestospongien (4), a known compound in N. exigua. The bisulphate avarol derivative (1) showed the most potent antibacterial effect, with the ability to inhibit Staphylococcus aureus at concentrations as low as 2.6 µg/mL, indicating its potential as a powerful antibacterial agent for drug development. Additionally, it exhibited strong bactericidal activity against Bacillus cereus and fungicidal activity against Candida albicans and Cryptococcus neoformans. Isohyrtiosine A (2), an indole alkaloid, exhibited moderate antimicrobial effects, while xestospongien (4) demonstrated broad-spectrum bacteriostatic activity. Demethylcystalgerone (3), a meroditerpenoid, showed selective activity against Gram-positive bacteria. These findings highlight the potential of N. exigua as a source of novel antimicrobial agents, particularly in combating antibiotic-resistant pathogens. Further research into the mechanisms of action and chemical diversity of sponge-derived compounds could lead to the development of new therapeutic agents for resistant infections.